Utilization of Filter Paper as an Innovative Transport Medium for Salmonella typhi and Shigella dysenteriae Bacteria: A Review of Effectiveness. - Atfal, Bustanul; Hijriani, Baiq Isti; Maola, Seftia Dhina (Jurnal Sain Veteriner, 2026)
The World Health Organization (WHO) released the Guidance on Regulations for the Transport of Infectious Substances 2023–2024 to minimize the risk of disease transmission caused by mishandling or leakage of infectious materials during transport. This initiative is reinforced by the Indonesian Directorate General of Civil Aviation, which restricts the amount of liquid material allowed on both domestic and international flights. In line with these policies, this study aimed to assess the effectiveness of filter paper as an alternative transport medium for Gram-negative bacteria, Salmonella typhi and Shigella dysenteriae, based on different storage durations at 37°C in the URB-Balitbangkes Laboratory in RSUP West Nusa Tenggara. The research employed an experimental laboratory design, using six samples with three repetitions, which resulted in 18 culture cups for each bacterium. Biochemical and Gram-staining tests confirmed positive results for both S. typhi and S. dysenteriae on the filter paper transport media. Bacterial growth remained consistent (+3) across all storage periods of 1, 2, 3, 4, 7, and 14 days. The findings demonstrate that filter paper can function effectively as a dry preservation medium, offering a practical and safe method for transporting infectious bacterial cultures over time.